Kinetic studies for DRM over high-performance NiâW/Al2O3âMgO catalyst - Yusuf, M. (Elsevier Ltd, 2021)
The reaction kinetics of DRM over high-performance NiâW/Al2O3âMgO bimetallic catalyst is investigated in a fixed bed reactor. The variation of reaction rate is examined within the CH4 and CO2 partial pressure from 0.2 to 0.6 atm and the temperature range of 600oCâ800 Â°C. It is found that the rate of reaction for DRM is more sensitive to CH4 partial pressure compared to CO2 partial pressures. At a constant partial pressure of CO2 and increasing the CH4 partial pressure, the increase in the reaction rate is more than reverse conditions. The activation energies of consumption of CH4 and CO2 were found to be 45.9 and 31.9 kJ/mol, respectively, showing a higher energy barrier for CH4 activation than CO2. Four typical kinetic models then fitted the experimental results obtained, i.e., Power Law, Langmuir- Hinshelwood and Eley-Rideal model I and II. The Langmuir-Hinshelwood model showed the best fitting between experimental and estimated reaction rates. Â© 2021 Hydrogen Energy Publications LLC